Applications of New Breeding Technologies for Potato Improvement - Hameed, Amir; Zaidi, Syed Shan-e-Ali; Shakir, Sara; Mansoor, Shahid (Frontiers in Plant Science, 2018)
The first decade of genetic engineering primarily focused on quantitative crop improvement. With the advances in technology, the focus of agricultural biotechnology has shifted towards both quantitative and qualitative crop improvement, to deal with the challenges of food security and nutrition. Potato (Solanum tuberosum L.) is a solanaceous food crop having potential to feed the populating world. It can provide more carbohydrates, proteins, minerals, and vitamins per unit area of land as compared to other potential food crops, and is the major staple food in many developing countries. These aspects have driven the scientific attention to engineer potato for nutrition improvement, keeping the yield unaffected. Several studies have shown the improved nutritional value of potato tubers, for example by enhancing Amaranth Albumin-1 seed protein content, vitamin C content, β-carotene level, triacylglycerol, tuber methionine content, and amylose content, etc. Removal of anti-nutritional compounds like steroidal glycoalkaloids, acrylamide and food toxins is another research priority for scientists and breeders to improve potato tuber quality. Trait improvement using genetic engineering mostly involved the generation of transgenic products. The commercialization of these engineered products has been a challenge due to consumer preference and regulatory/ethical restrictions. In this context, new breeding technolgies like TALEN (transcription activator-like effector nucleases) and CRISPR/Cas9 (clustered regularly interspaced palindromic repeats / CRISPR-associated 9) have been employed to generate transgene-free products in a more precise, prompt and effective way. Moreover, the availability of potato genome sequence and efficient potato transformation systems have remarkably facilitated potato genetic engineering. Here we summarize the potato trait improvement and potential application of new breeding technologies to genetically improve the overall agronomic profile of potato.